REPLACEMENT PAGE ON THE OPERATING SYSTEM APPLICATION PROGRAM USING PASCAL - Agha Nugraha; Don Elsyafitri, Ir, SKom (Jurnal Sistem Informasi, 2002)
The information inside or outside the record in the computer memory. In other words, memory is a tool on a computer system that served to store information. Duty to accommodate working memory tasks in the time before and during after the work is carried out by the processor. While Memory Memory support or virtual created to support or assist Memory-work. Loading rates in the framework of a working memory which will cause all the order filled. After that, if there is a new tribe who need a place in the working memory is no longer able to accommodate the placement of another tribe. In order for the new rates can be accommodated within the working memory, there is interest in the context of working memory capacity should be restored to memory.